Comparison of clot lysis activity and biochemical properties of originator tenecteplase (Metalyse®) with those of an alleged biosimilar - Werner eKliche; Ingo eKrech; Martin C Michel; Martin C Michel; Nishant V Sangole; Sadhana eSathaye (Frontiers Media S.A., 2014)
The bioengineered tissue plasminogen activator tenecteplase is an important treatment modality of acute myocardial infarction recommended by international guidelines. Following introduction of originator tenecteplase (brand names Metalyse® and TNKase®), a 'biosimilar' tenecteplase became available for commercial use in India under the brand name Elaxim® in the absence of Indian biosimilar guidelines which came into force from September 15th, 2012. Based on a report of biochemical and fibrinolytical differences between Metalyse and Elaxim, we have systematically compared them in a range of routine quality testing assays. As compared to Metalyse, Elaxim exhibited less clot lysis activity and contained less of the two-chain form of tenecteplase. Even upon full in vitro conversion to the two-chain form Elaxim exhibited less clot lysis activity. This was linked to differences in sialic acid content and glycosylation pattern with Elaxim exhibiting less bi- and more tetra-antennary glycosylation, leading to different charge heterogeneity profile. Regarding purity, Elaxim contained more tenecteplase aggregates and, in contrast to Metalyse, considerable amounts of Chinese hamster ovary cell protein. Taken together these data demonstrate that Metalyse and Elaxim differ considerably in clot lysis activity and biochemical properties. These data question whether Elaxim indeed can be considered a 'biosimilar' of Metalyse, i.e. whether and to which extent the clinical efficacy and safety properties of Metalyse can be extrapolated to Elaxim in the absence of comparative clinical data.